2010
DOI: 10.1021/cb100144v
|View full text |Cite
|
Sign up to set email alerts
|

Retinol and Retinol-Binding Protein Stabilize Transthyretin via Formation of Retinol Transport Complex

Abstract: Transthyretin (TTR) is a plasma hormone carrier protein associated with hereditary and senile forms of systemic amyloid disease, wherein slow tetramer disassembly is thought to be an obligatory step. Plasma transport of retinol is carried out exclusively by the retinol-binding protein (RBP), through complexation with transthyretin. Using mass spectrometry to examine the subunit exchange dynamics, we find that retinol stabilizes the quaternary structure of transthyretin, through its interactions with RBP, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…The dynamics of the L7/L12 proteins were investigated using an MS strategy that has proven successful to elucidate the subunit exchange dynamics of other protein complexes (30)(31)(32)(33). Specifically, ribosomes are uniformly labeled with stable isotopes ( 13 C and 15 N) to provide sufficient mass differences to resolve heterocomplexes formed with wild-type ribosomes.…”
Section: Isotopically Labeled Ribosomes Maintain Interactionsmentioning
confidence: 99%
“…The dynamics of the L7/L12 proteins were investigated using an MS strategy that has proven successful to elucidate the subunit exchange dynamics of other protein complexes (30)(31)(32)(33). Specifically, ribosomes are uniformly labeled with stable isotopes ( 13 C and 15 N) to provide sufficient mass differences to resolve heterocomplexes formed with wild-type ribosomes.…”
Section: Isotopically Labeled Ribosomes Maintain Interactionsmentioning
confidence: 99%
“…Additionally, the rapid analysis possible with ESI-MS makes it convenient for following subunit exchange in real time [38]. Despite these benefits, only a small number of studies applying ESI-MS to multimeric protein subunit exchange have been reported [39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of these studies to larger group numbers would confirm our findings and further demonstrate the utility of RBP4 as a biomarker of ATTRm cardiac amyloid disease. Moreover, this study did not include examination of serum vitamin A levels, potentially important as retinol is a key player in the recognition and binding of RBP4 to TTR [4,21,41]. Unfortunately, accurate measurement of vitamin A is challenging as levels are homeostatically controlled (50-200 g/dL) [42] and serum retinol concentrations are only an indirect reflection of total vitamin A in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…RBP4-TTR complexes are formed in the ER [1,2] and their release from the liver into circulation is dependent on retinol binding to RBP4 [3]. Consequently, 95% of circulating RBP4 is bound to TTR [4,5]. The serum concentration is normally 42 µg/mL, but elevated levels have been described in type 2 diabetes [6], obesity [7], and inflammatory cardiomyopathy [8].…”
Section: Introductionmentioning
confidence: 99%